[PP.36.04]: USEFULNESS OF SLOW BREATHING TRAINING IN CHRONIC HEART FAILURE. STUDY DESIGN AND INTERMEDIATE RESULTS. (June 2015) - Debicka-Dabrowska>, D.>; Lisi, E.; Drozdz, T.; Styczkiewicz, K.; Malfatto, G.; Salerno, S.; Bednarek, A.; Olszanecka, A.; Kielbasa, G.; Bilo, G.; Czarnecka, D.; Kawecka-Jaszcz, K.; et al.
Abstract : Objective: Slow breathing has favorable acute effects in chronic heart failure (CHF) patients. Aim of this study is to test the feasibility and efficacy of a new nonpharmacological CHF treatment method based on slow breathing training (SBT). Design and method: The study is an ongoing cross-over open trial where patients, in random order, undergo a 10–12 week period of SBT with RESPeRATE device (InterCure Ltd., Lod, Israel) and a 10–12 week follow-up under usual care. Patients randomized to SBT are asked to perform each day two separate 15-min sessions of device-guided SBT at a breathing frequency of 6 breaths per minute. In all patients, clinical data collection, polysomnography, 6 minute walking test (6MWT), 24-h Holter ECG monitoring, Minnesota quality of life questionnaire and laboratory tests are performed at baseline and after each study phase. Results: Until now 97 pts have entered the study with the following baseline characteristics: age 66.3 ± 10.9 years, 76 M/21F, 43 with ischemic CHF, NYHA Class I: 4, Class II:52, Class III:3, left ventricular ejection fraction 30.1 ± 6.9%, hypertension:23, history of stroke:5, diabetes:16, apnea-hypopnea index (AHI) 10.3 ± 10.5. So far 60 of them have completed the study. No patients had relevant intervention-related adverse events in the course of the study (2 of them underwent CRT pacemaker implantation, 1 had myocardial infarction without time relation to SBT). Compared with baseline values in subjects who completed SBT phase, 6MWT distance (438 ± 126 vs 448 ± 141, p = 0.015) and LV ejection fraction (31.1 ± 6.8 vs 32.8 ± 6.5, p < 0.005) increased; AHI (9.81 ± 9.52 vs 8.1 ± 9.5, p = 0.027) and NYHA scale decreased (1.98 ± 0.35 vs 1.46 ± 0.50, p < 0.001); no significant changes occurred in NT-proBNP (1293 ± 1555 vs 1214 ± 1555, p = 0.92) or BNP (240 ± 173 vs 227 ± 195, p = 0.49). Conclusions: Preliminary data indicate that SBT is feasible and safe in CHF subjects and suggest an improvement in functional capacity and in sleep disordered breathing severity. If these results are confirmed in a larger sample, they may support SBT as a novel and useful component of cardiorespiratory rehabilitation programmes in CHF.